2009
DOI: 10.1590/s1806-83242009000300013
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal behavioral analysis during dental care of children aged 0 to 3 years

Abstract: 302Longitudinal behavioral analysis during dental care of children aged 0 to 3 years Abstract: "When" and "how" the dentist intervenes have repercussions on children's physical and emotional patterns. The objective of the present study was to conduct a longitudinal behavioral analysis during dental care of babies aged 0 to 3 years. A total of 216 patients seen at the Baby Clinic of the School of Dentistry at Araçatuba, São Paulo State University (UNESP), were selected. The selection criterion was attendance at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…Among the results, 79% of parents think that child's age has influence in their behaviour in dental clinics. Longitudinal behaviour analysis studies conducted by Cunha and his colleagues showed that child undergoing dental care was directly influenced by child's psychomotor development [15].…”
Section: Discussionmentioning
confidence: 99%
“…Among the results, 79% of parents think that child's age has influence in their behaviour in dental clinics. Longitudinal behaviour analysis studies conducted by Cunha and his colleagues showed that child undergoing dental care was directly influenced by child's psychomotor development [15].…”
Section: Discussionmentioning
confidence: 99%
“…A child’s ability to control his or her own behavior to cooperate for a procedure depends both on his or her chronologic and developmental age. 40 …”
Section: Discussionmentioning
confidence: 99%
“…However, child distress during medical and dental procedures is common and likely due to the child’s natural wariness of unfamiliar situations and people, immature communication skills, and developing emotional stability. (Cunha et al 2009) Medical procedures perceived to be necessary yet painful and distressing to young children, including immunizations, venipuncture, and cancer treatments, have been the subject of extensive investigation. (Blount et al 1991; Blount et al 2008b; Chambers et al 2009; Frank et al 1995; Mahoney et al 2010; McMurtry et al 2007; McMurtry et al 2010; Zhou et al 2013) The shared goal of these studies was to identify ways to reduce distress and disruptive behavior of paediatric patients.…”
Section: Introductionmentioning
confidence: 99%